Citations in Economics: Measurement, Uses and Impacts - Daniel S. Hamermesh (Institute for the Study of Labor (IZA), 2015)
I describe and compare sources of data on citations in economics and the statistics that can be constructed from them. Constructing data sets of the post-publication citation histories of articles published in the "Top 5" journals in the 1970s and the 2000s, I examine distributions and life cycles of citations, compare citation histories of articles in different sub-specialties in economics and present evidence on the history and heterogeneity of those journals' impacts and the marginal citation productivity of additional coauthors. I use a new data set of the lifetime citation histories of over 1000 economists from 30 universities to rank economics departments by various measures and to demonstrate the importance of intra- and interdepartmental heterogeneity in productivity. Throughout, the discussion summarizes earlier work. I survey research on the impacts of citations on salaries and non-monetary rewards and discuss how citations reflect judgments about research quality in economics.
Keywords: A11; J01; B31; 330; academic productivity; tournaments; publication; rankings